Chronic Trypanosoma cruzi infection potentiates adipose tissue macrophage polarization toward an anti-inflammatory M2 phenotype and contributes to diabetes progression in a diet-induced obesity model - Cabalén, María Eugenia (2016)
Chronic obesity and Chagas disease (caused by the protozoan Trypanosoma cruzi) represent serious public health concerns. The interrelation between parasite infection, adipose tissue, immune system and metabolism in an obesogenic context, has not been entirely explored. A novel diet-induced obesity model (DIO) was developed in C57BL/6 wild type mice to examine the effect of chronic infection (DIO+I) on metabolic parameters and on obesity-related disorders. Dyslipidemia, hyperleptinemia, and cardiac/hepatic steatosis were strongly developed in DIO mice. Strikingly, although these metabolic alterations were collectively improved by infection, plasmatic apoB100 levels remain significantly increased in DIO+I, suggesting the presence of pro-atherogenic small and dense LDL particles. Moreover, acute insulin resistance followed by chronic hyperglycemia with hypoinsulinemia was found, evidencing an infection-related-diabetes progression. These lipid and glucose metabolic changes seemed to be highly dependent on TLR4 expression since TLR4-/- mice were protected from obesity and its complications. Notably, chronic infection promoted a strong increase in MCP-1 producing macrophages with a M2 (F4/80+CD11c-CD206+) phenotype associated to oxidative stress in visceral adipose tissue of DIO+I mice. Importantly, infection reduced lipid content but intensified inflammatory infiltrates in target tissues. Thus, parasite persistence in an obesogenic environment and the resulting host immunometabolic dysregulation may contribute to diabetes/atherosclerosis progression.